Wnt signaling in the mouse heart: a role for Wnt11 in cardiogenesis - Abdul-Ghani, Mohammad (University of Ottawa (Canada), 2010)
Specification and early patterning of the vertebrate heart is dependent on both canonical and non-canonical wingless (Wnt) signal pathways, however, the impact of each Wnt pathway on the later stages of myocardial development and differentiation remains contentious. Here, we sought to define the respective roles of canonical and non-canonical Wnt signaling during mammalian cardiogenesis, specifically cardiomyocyte differentiation and maturation. The cellular components of both canonical and non-canonical Wnt pathways were present throughout murine cardiac development, yet canonical Wnt signaling had a restricted region of activity in the mouse heart, primarily in the non-myocardial regions including the outflow tract and semi-lunar valves. Conversely, elevated non-canonical Wnt11 signaling was associated with expansion of the myocardium and de novo induction of cardiomyocyte differentiation. The pro-myogenic effect of Wnt11 resulted in a direct inhibition of canonical Wnt/beta-catenin activity in Wnt11-treated progenitor cells suggesting that non-canonical signaling enhanced cardiogenesis through suppression of canonical Wnt pathways. Wnt11 stimulation suppressed canonical Wnt signaling by destabilizing full length beta-catenin, an effect that could be reversed by inhibiting caspase 3/8 activity. Stimulation of progenitor cells with Wnt11 promoted the activation of caspase 3/8 and inhibition of either protease resulted in inhibition of cardiomyocyte differentiation. Taken together, our results suggest that non-canonical Wnt11 signaling promotes cardiogenesis, in part, by caspase-mediated suppression of canonical Wnt/beta-catenin activity.
Keywords: Biology, Molecular.